Biomethane production from low-strength wastewater in an upflow anaerobic sludge blanket reactor modelling methane production kinetics using sigmoidal growth functions and determining the effects of hydraulic retention time and reactor height on extracellular polymeric substances - Ebrada, Leni C.
Anaerobic digestion converts biodegradable organic materials or biomass into bio-gas which is primarily composed of biomethane, an alternative energy resource which can be used to fuel vehicles and/or to generate heat and electricity. One important component of anaerobic digesters is the anaerobic sludge, composed of granules and/or flocs containing the microogranisms which degrades the organic components of the substrate. One of the most crucial factors determining success of microbial aggregation is the extracellular polymeric substances (EPS) production since EPS has the capacity to protect the microorganisms from harsh environment such as very low organic initial substrate concentration (or low-strength wastewater). Firstly, fed-batch experiment was conducted to determine the effect of carbon to nitrogen (C/N) ratio, which has been noted to affect EPS production. The different levels of C/N ratio were: 3.33, 13.33, 26.67 and 53.33. It was observed that nitrogen deficiency and excess results to higher EPS production. The highest EPS content (17.79±1.24 mg EPS (g VS)-1) was obtained from granules subjected to C/N ratio of 3.33. This C/N ratio was used to prepare the synthetic wastewater for the low-strength wastewater treatment. One of the challenges in anaerobic digestion using upflow anaerobic sludge blanket (UASB) reactor is the treatment of low-strength wastewater. In this study, the performance of a lab-scale upflow anaerobic sludge blanket reactor treating sucrose wastewater with initial substrate concentration of 0.3 g COD L -1 was investigated under different hydraulic retention times (HRT). The reactor was first operated at HRT of 24 h for 11 days, 12 h for 31 days, 6 h for 20 days and finally, 4 h for 20 days. The first 42 days is considered as start-up. At the end of the run for HRT of 6 h and 4 h, granule samples were obtained from two different positions along the vertical axis of the reactor, revealing variations in the amounts of sugar/protein ratio of the EPS and total EPS. Protein was found to be the larger component of EPS. Furthermore the highest values of protein content (7.02 mg (g VS)-1) and total EPS (9.39 mg (g VS)-1) were obtained at the lower part of the reactor at HRT of 6 h. The biogas produced from the anaerobic digestion of low-strength wastewater was collected and measured daily. The dissolved bio-methane in the effluent was calculated. The cumulative bio-methane production was fitted with sigmoidal growth curves: logistic function and modified Gompertz kinetic models. The experimental data fit with both models with coefficient of determination r2 >0.989. The models were modified by expressing maximum cumulative yield Pmax and maximum specific methane yield Rm in terms of HRT. Pmax and HRT follows an exponential decay model whereas Rm and HRT fits with power model curve.